( E )-3,4,5-Trimethoxy- N ′-[(6-methoxy-4-oxo-4 H -chromen-3-yl)methylidene]benzohydrazide monohydrate - Ishikawa, Yoshinobu; Watanabe, Kohzoh (Acta crystallographica. Section E, Structure reports online, 2014)
In the title chromone-tethered benzohydrazide derivative, C 21 H 20 N 2 O 7 ·H 2 O, the atoms of the 4 H -chromen-4-one segment are essentially coplanar (r.m.s. deviation = 0.0073 Å) with the largest deviation from the mean plane [0.012 (3) Å] being found for the benzene C atom. The dihedral angles between the chromone segment and the hydrazide plane and between the chromone segment and the benzene ring of the trimethoxybenzene unit are 24.67 (9) and 41.28 (8) Å, respectively. The molecule is connected to the solvent water molecule by O—H...O hydrogen bonds and weak C—H...O interactions. Additional N—H...O interactions are observed and together they link the molecules into chains forming a two-dimensional network along (011).